High Prevalence of Common Human Viruses in Thyroid Tissue - Weider, Therese; Genoni, Angelo; Broccolo, Francesco; Paulsen, Trond H.; Dahl-Jørgensen, Knut; Toniolo, Antonio; Hammerstad, Sara Salehi (Frontiers in Endocrinology, 2022)
Introduction Evidence points to viral infections as possible triggers of autoimmune thyroid disease (AITD), but little is known about the prevalence of common viruses in the thyroid gland. Using a novel approach based on virus enrichment in multiple cell lines followed by detection of the viral genome and visualization of viral proteins, we investigated the presence of multiple human viruses in thyroid tissue from AITD patients and controls. Methods Thyroid tissue was collected by core needle biopsy or during thyroid surgery from 35 patients with AITD (20 Graves’ disease and 15 Hashimoto’s thyroiditis). Eighteen thyroid tissue specimens from patients undergoing neck surgery for reasons other than thyroid autoimmunity served as controls. Specimens were tested for the presence of ten different viruses. Enteroviruses and human herpesvirus 6 were enriched in cell culture before detection by PCR and immunofluorescence, while the remaining viruses were detected by PCR of biopsied tissue. Results Forty of 53 cases (75%) carried an infectious virus. Notably, 43% of all cases had a single virus, whereas 32% were coinfected by two or more virus types. An anterovirus was found in 24/53 cases (45%), human herpesvirus 6 in 17/53 cases (32%) and parvovirus B19 in 12/53 cases (22%). Epstein-Barr virus and cytomegalovirus were found in a few cases only. Of five gastroenteric virus groups examined, only one was detected in a single specimen. Virus distribution was not statistically different between AITD cases and controls. Conclusion Common human viruses are highly prevalent in the thyroid gland. This is the first study in which multiple viral agents have been explored in thyroid. It remains to be established whether the detected viruses represent causal agents, possible cofactors or simple bystanders.